2019
DOI: 10.1016/j.jaac.2019.02.019
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Microstructure in Youths With Conduct Disorder: Effects of Sex and Variation in Callous Traits

Abstract: Objective: Studies using diffusion tensor imaging (DTI) to investigate white matter (WM) microstructure in youths with conduct disorder (CD) have reported disparate findings. We investigated WM alterations in a large sample of youths with CD, and examined the influence of sex and callousunemotional (CU) traits. Method: DTI data were acquired from 124 youths with CD (59 female) and 174 typically developing (TD) youths (103 female) 9 to 18 years of age.Tract-based spatial statistics tested for effects of diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 58 publications
(113 reference statements)
5
13
0
Order By: Relevance
“…On the other hand, the larger sample size and the multi-center approach might have increased the reliability and generalizability of our results. Finally, sex-dependent effects were supported by our exploratory analyses, in line with earlier brain imaging studies on aggressive behavior [ 63 ]. They should be investigated more in-depth in the future in study samples with comparable sex distributions.…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, the larger sample size and the multi-center approach might have increased the reliability and generalizability of our results. Finally, sex-dependent effects were supported by our exploratory analyses, in line with earlier brain imaging studies on aggressive behavior [ 63 ]. They should be investigated more in-depth in the future in study samples with comparable sex distributions.…”
Section: Discussionsupporting
confidence: 87%
“…The construct of subtypes within anti-social youth, with marked psychiatric vulnerabilities, resonates with results from this study and is echoed in current research into the CU traits, childhood-onset CD and neuroscientific differences in the brains of young people exhibiting CU traits (Hughes et al , 2015; Rogers et al , 2019; Milone et al , 2019). The CU traits are recognized as increasing the likelihood of severe CD and violent offending (Waller et al , 2020).…”
Section: Discussionsupporting
confidence: 77%
“…Table S1 in Supplementary Materials provides an overview of the 52 studies published from 2015 to 2020, included in the review for analysis. Among the 52 studies, most authors reported results on more than one dimension of the model, e.g., [ 69 , 70 ], 47 reported effects on mental health, e.g., [ 71 , 72 , 73 ] or on neurobiological features, e.g., [ 69 , 74 , 75 ], 22 on social contexts, e.g., [ 36 , 76 ], eight on social adjustment, e.g., [ 77 , 78 ], 10 on social roles and social interactions, e.g., [ 79 , 80 ] and 19 on executive functions or cognition, e.g., [ 81 , 82 ]. The majority (k = 17) were carried out in the USA, e.g., [ 83 , 84 ], two in Canada [ 70 , 85 ], two in Australia, two in Israel, the one in Europe (Spain, Germany, Netherlands, etc.).…”
Section: Resultsmentioning
confidence: 99%
“…The majority (k = 17) were carried out in the USA, e.g., [ 83 , 84 ], two in Canada [ 70 , 85 ], two in Australia, two in Israel, the one in Europe (Spain, Germany, Netherlands, etc.). Four studies were conducted in Switzerland in partnership with other countries, e.g., [ 82 , 86 ]. The review did not allow to identify any study, including a French-speaking sample.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation